2005
DOI: 10.1124/mol.105.016055
|View full text |Cite
|
Sign up to set email alerts
|

A Prodrug of Cysteine, l-2-Oxothiazolidine-4-carboxylic Acid, Regulates Vascular Permeability by Reducing Vascular Endothelial Growth Factor Expression in Asthma

Abstract: Inflammation of the asthmatic airway is usually accompanied by increased vascular permeability and plasma exudation. Oxidative stress plays critical roles in airway inflammation. Although reactive oxygen species (ROS) are shown to cause vascular leakage, the mechanisms by which ROS induce increased vascular permeability are not clearly understood. We have used a murine model of asthma to evaluate the effect of L-2-oxothiazolidine-4-carboxylic acid (OTC), a prodrug of cysteine that acts as an antioxidant, more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 50 publications
3
16
0
2
Order By: Relevance
“…These results suggest that ROS signaling is associated with the regulation of IL-18 expression and that treatment of the antioxidants may improve the asthmatic features via regulation of IL-18 expression. Consistent with this present study, several studies have demonstrated that antioxidants are able to reduce airway inflammation and hyperresponsiveness through the regulation of NF-B activity and modulate vascular permeability by lowering vascular endothelial growth factor expression in animal models of asthma (Cho et al, 2004;Lee et al, 2004Lee et al, , 2005.…”
Section: Discussionsupporting
confidence: 89%
“…These results suggest that ROS signaling is associated with the regulation of IL-18 expression and that treatment of the antioxidants may improve the asthmatic features via regulation of IL-18 expression. Consistent with this present study, several studies have demonstrated that antioxidants are able to reduce airway inflammation and hyperresponsiveness through the regulation of NF-B activity and modulate vascular permeability by lowering vascular endothelial growth factor expression in animal models of asthma (Cho et al, 2004;Lee et al, 2004Lee et al, , 2005.…”
Section: Discussionsupporting
confidence: 89%
“…VEGF increases vascular permeability, resulting in the leakage of plasma proteins into the extravascular space, which leads to edema and profound alterations in the extracellular matrix. Previous studies have shown that overproduction of VEGF is associated with an augmentation of vascular permeability and plasma exudation in a murine model of pulmonary inflammation, which induces overproduction of ROS in the airways (Lee et al, 2005(Lee et al, , 2006. In this study, we have found that expression of VEGF protein was upregulated and vascular permeability was also increased and that there was a close correlation between VEGF levels and vascular permeability in H 2 O 2 -induced acute lung injury.…”
Section: Discussionsupporting
confidence: 60%
“…We have previously demonstrated that HIF-1α protein levels increased after H 2 O 2 inhalation were decreased significantly by administration of PI3K inhibitors and that an HIF-1α inhibitor significantly reduced the increase of VEGF expression in lungs of H 2 O 2 -inhaled mice (Lee et al, 2006). In addition, administration of antioxidants, L-2-oxothiazolidine-4-carboxylic acid and α-lipoic acid, markedly attenuates augmentation of PI3K activity, nuclear HIF-1α levels, and VEGF levels in a murine model of ROS-induced lung injury (Lee et al, 2005(Lee et al, , 2006. Consistent with the previous findings (Lee et al, 2006), present results have revealed that Akt phosphorylation and PI3K activity in lung tissues and HIF-1α protein levels in nuclear extracts were increased after H 2 O 2 inhalation and that the administration of COMP-Ang1 attenuated the augmentation of PI3K activity and nuclear HIF-1α levels.…”
Section: Discussionmentioning
confidence: 91%
“…Level of ROS has been shown to be increased in the airways of OVA-challenged animals (Nishida et al, 2002;Zhang et al, 2002;Lee et al, 2004dLee et al, , 2005Lee et al, , 2006a. ROS released by inflammatory cells infiltrating the airways play an important role in the airway tissue injury observed in asthma (Dworski, 2000).…”
Section: Discussionmentioning
confidence: 99%